A lidar assisted feedforward preview controller for load mitigation in wind turbines - Luciano Xavier Pereira (2015)
The advancement of renewable energies is dependent on the reduction of the costs involved. One way to diminish the maintenance costs and increase the lifetime of wind turbines is to mitigate the loads and fatigue experienced by their components. Present commercial wind turbine control systems rely usually on feedback. As the control system can act only on errors that are already present, the regulation quality is restricted due to the large rotor inertia. In this work a H2 feedforward blade pitch controller is designed using an algorithm optimized for preview control. The used design method is more computationally efficient and numerically stable than the ones adopted in the preceding literature. The control objectives of the feedforward controller are to regulate the generator speed, reduce tower loads and preserve the pitch system. The controller input is a previewed effective wind speed estimate measured by a LIDAR detector. The validation of the system performance is made with aeroelastic simulations of a reference wind turbine equipped with both baseline and feedforward-enhanced controllers. The simulations are made using the FAST simulator with input wind provided by TurbSim. The results show that the designed controller is able to reduce generator speed fluctuations, tower loads and pitch activity without reducing the generated power, contributing to the turbine lifetime and hence decreasing the cost of energy. The work indicates the feasibility and effectiveness of the design technique and lays ground for future works on the area of feedforward wind turbine pitch control.